Stability of stratified elastico-viscous Walters' (Model B') fluid in the presence of horizontal magnetic field and rotation in porous medium (Archives of Mechanics - Test, 2006)
Combined effect of magnetic field and rotation is considered on the stability of stratified visco-elastic Walters' (Model B') fluid in porous medium. In contrast to the Newtonian fluids, the system is found to be unstable at stable stratification for low values of permeability or high values of kinematic viscoelasticity. Magnetic field is found to stabilize the small wavelength perturbations for unstable stratification. Variation of growth rate in the case of unstable stratification is depicted graphically with the variation in viscosity, viscoelasticity and permeability. It has been found that the growth rate increases with the increase in kinematic viscosity and permeability, whereas it decreases with the increase in kinematic viscoelasticity.